Mechanisms and Management Strategies for Satsuma Mandarin Fruit Cracking - Yongjie Li; Guoqiang Jin; Mingxia Wen; Xiaoting Zhu; Yongqiang Zheng (Agronomy)
The Satsuma mandarin, a prominent fresh citrus variety cultivated in Asia, is susceptible to fruit cracking, a physiological disorder that significantly impacts yield and economic efficiency. This phenomenon occurs during the fruit expansion phase. The present study sought to further elucidate the correlation between citrus fruit cracking and fruit peel development or mineral elements, as well as to propose efficacious management measures. The present experiment was conducted on Citrus unshiu Marc. cv. ‘Miyagawa Wase’ over two successive seasons—2022 and 2023. The dynamic changes in fruit morphology were recorded using calipers, and the peel strength was assessed via a Plus Texture Analyzer. Paraffin sectioning technology was used to observe the morphological structure of peel cells. At 10 days after full bloom (DAFB), the peel cells exhibited vigorous proliferation, and the fruit and peel thicknesses underwent rapid expansion. At 50–60 d after full bloom, the longitudinal and transverse diameters of the fruit exhibited a marked increase in the growth rate of the former over the latter. At 80 d after full bloom, both the peel thickness change and the fruit growth rate exhibited a marked deceleration, and the albedo layer cells began to show signs of perforation. The following two time points were preliminarily proposed as the key points for the control of citrus fruit cracking: key point one was 50–60 days after full bloom; and key point two was 80–90 days after full bloom. The nitrogen (N), phosphorus (P), and potassium (K) contents in the different orchards were measured via the semi-micro Kjeldahl nitrogen method, the molybdenum–antimony colorimetric method, and flame photometry, respectively. The determination of other mineral elements was conducted by means of inductively coupled plasma spectroscopy. Principal component analysis was employed to analyze the 21-parameter indices of mineral elements in soil and leaf samples from the three orchards with different levels of fruit cracking. The study found that high concentrations of leaf Fe, P, and soil Cu, as well as organic matter content, contributed negatively to the extent of fruit cracking. The impact of diverse control measures on the incidence of fruit cracking was subsequently observed, following the implementation of tree crown spray treatments. The application of 0.5% calcium superphosphate and 0.006% EDTA-Fe, in combination with 10 ppm GA3 sprayed during two critical periods, significantly reduced fruit cracking and did not adversely affect the internal or external quality of the fruits. The study emphasises the necessity of customising management measures according to the developmental characteristics of citrus fruits, given the observed varietal and regional distinctions in susceptibility to cracking. These findings are pivotal for advancing research in the field of fruit cracking and promoting the healthy development of the industry.